FORENSIC ACCOUNTANTS’ DETERMINANTS IN INDONESIA: ERADICATION OF CORRUPTION THROUGH AUDIT TO CALCULATE STATE FINANCIAL LOSSES - Evenri Sihombing; Erlina; Iskandar Muda; Khaira Amalia Fachrudin (The American Journal of Interdisciplinary Innovations and Research, 2024)
The research aims to assess forensic accountants' determinants of the audit quality to calculate state financial losses (APKKN) related to corruption case in Indonesia. The locus are forensic accountants at BPKP who have experienced in trials of corruption. The lawsuit risks for organizations and individual are part of the major risk in conducting APKKN. APKKN is categorized as a sub-specialist audit related to the litigation. The research was quantitative method with 364 auditors as respondents. Data are processed by the WarpPLS 8.0. The findings shows that all variables including rotation, synergy, and pursuit of evidence have effect on the quality of APKKN except for audit costs. In line with that, the pursuit evidence is significantly affected by rotation and synergy except for audit costs. Additionally, the pursuit of evidence doesn’t mediate audit cost and audit rotation, but it mediates synergy and APKKN quality. Rotation and synergy are presented as new complements to goal theory beside individual intentions and values. This research also partially confirmed forensic accounting theory, since the capability signal, materiality, bonuses, anonymity, and unsustainability (collapse) are unfounded.